Heterogeneity and optimization of ecological security pattern on a mountain town: A case of Tianzhu County in the Hexi Corridor, China - Chen, Zhijie; Chen, Hong; Yang, Minan; Wang, Xi; Jiang, Yuefeng; Zhang, Wei (Frontiers in Environmental Science, 2023)
As a primary concern in the ecosystem, understanding the impact of spatial heterogeneity of ecological networks on the development of environmental sustainability has overarching significance. The Tibetan Plateau’s edge is a vital contribution to the study of the plateau’s ecological network. However, there are few studies and explorations on the county-level ecological network in the arid region. This study aimed to evaluate ecological network spatial patterns in Tianzhu County and establish an ecological security evaluation index system. We used the minimum cumulative resistance (MCR) model and built an ecological resistance surface model from the exploratory spatial data analysis (ESDA) method. Then, by identifying ecological corridors and ecological nodes from the gravity model, we analyzed the ecological security pattern and proposed specific plans for optimizing the situation. The results showed that 1) county ecological security overall has been lower, and its values showed spatial heterogeneity in each direction, and 2) the Z-Score of the ecological security evaluation index was 70.1893, which shows ecological vulnerability in the arid region has significant spatial autocorrelation. The study identified 156 ecological corridors and 112 ecological nodes, which formed an ecological spatial pattern of “one belt and three zones.” Our analytical framework offers a valuable tool for constructing ecological security patterns in Tianzhu County and selecting “sources” at the regional scale, which can be applied to landscapes and geographical contexts for sustainable development in arid regions.